Longitudinal relationships between motivation types and heart failure self-care - Yasser Saeedian; Paul Jansons; Matthew Fuller-Tyszkiewicz; Ralph Maddison (BMC Psychology, 2026)
Abstract Background Self-care is essential for long-term heart failure (HF) management, but many people with HF struggle to engage with self-care activities over time. This may be because of motivational factors in HF management. Self-Determination Theory (SDT) offers a robust theoretical framework for understanding the relationship between motivation and self-care; however, it is unclear whether motivation predicts self-care of HF over time. Objectives A longitudinal study was conducted to examine the relationship between motivations and self-care over time. Methods This study included a baseline questionnaire (T1) and a 3-month follow-up questionnaire (T2). Results One hundred one participants (60 females) completed the baseline questionnaire, and 81 participants (46 females) completed the follow up questionnaire. Higher autonomous motivation at T1 was significantly associated with higher self-care at T1 and was indirectly associated with higher self-care at T2 through two pathways: higher self-care at T1 and higher autonomous motivation at T2. In contrast, controlled motivation and amotivation showed no statistically significant direct or indirect associations with self-care. Exploratory analyses also indicated that higher autonomous motivation at T1 was associated with lower amotivation at T2. Conclusions This study highlighted the stability of motivation types and the crucial role of autonomous motivation in predicting self-care over time. These findings emphasised the need to prioritise strategies that enhance autonomous motivation when designing interventions to support long-term self-care in HF.